KALIMAT MAJEMUK BAHASA MINANGKABAU DALAM KABA - Efri Yades (Universitas Andalas, 2013)
The paper examines the use of Minangkabau language compound sentences in kaba as literatur creation of Minangkabaunesse. The research was conducted to identify the kind of compound sentences used in kaba and to explain the structure. Based on the research, it is found compound sentences which are used in kaba are three kinds namely: cootdinative compound sentences, subordinative compound sentences, and combined compound sentences. Beside that, based on the amount of clauses it found that compound sentences consist of 3 clauses, 4 clauses, 5 clauses, 6 clauses, 7 clauses, 8 clauses, and 9 clauses. On the other hand, compound sentenses in kaba use conjungtion namely: jo ‘and’, sarato ‘and’, namum ‘but’, lalu ‘than’, sasudah ‘after’, kok ‘if’, and dek ‘because. Minangkabau language compound sentences in kaba use structure namely: P-S,P-P-K; Konj-P-Pel-Konj-Pel-Ket,S-S-P,S-P,S-P; P-S,P-S,P-S,Ket-S,Ket-S; P-S,P-S,P-S,Ket-S,Ket-S; Ket-P,P-O,P-Pel,P-Pel-Ket; P-O,P-S,P-Ket,S-P; Ket-P-S,P-Ket, P-Ket; P-Ket,P-S-Ket,Ket-P-Ket,P-P,P-Ket,P-Ket,S-P-Pel,Ket-Ket,S-P.